Probing the electron-to-proton mass ratio gradient in the Milky Way with Class I methanol masers. Issue 1 (11th January 2022) - Levshakov, S A; Agafonova, I I; Henkel, C; Kim, Kee-Tae; Kozlov, M G; Lankhaar, B; Yang, W
ABSTRACT: We estimate limits on non-universal coupling of hypothetical hidden fields to standard matter by evaluating the fractional changes in the electron-to-proton mass ratio, μ = m e / m p, based on observations of Class I methanol masers distributed in the Milky Way disc over the range of the Galactocentric distances 4 R 12 kpc. The velocity offsets Δ V = V 44 − V 95 measured between the 44- and 95-GHz methanol lines provide, so far, one of the most stringent constraints on the spatial gradient k μ ≡ d(Δμ/μ)/d R < 2 × 10 −9 kpc −1 and the upper limit on Δμ/μ <2 × 10 −8, where Δμ/μ = (μ _obs-μ _lab)/μ _lab . We also find that the offsets Δ V are clustered into two groups which are separated by δ _Δ V = 0.022 ± 0.003 km s −1 (1σ confidence level). The grouping is most probably due to the dominance of different hyperfine transitions in the 44- and 95-GHz methanol maser emission. Which transition becomes favoured is determined by an alignment (polarization) of the nuclear spins of the four hydrogen atoms in the methanol molecule. This result confirms that there are preferred hyperfine transitions involved in the methanol maser action.